2021
DOI: 10.3390/foods10061346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flutriafol Fungicide on the Lipid Accumulation in Human Liver Cells and Rat Liver

Abstract: Flutriafol (FTF) is a triazole fungicide that can cause liver toxicity through the ingestion of its residues in food and water. However, little is known about the liver toxicity of FTF, particularly nonalcoholic fatty liver disease (NAFLD) in humans. Therefore, the purpose of this study was to investigate whether FTF induces NAFLD in human liver cells and animal liver. HepG2 cells and Sprague Dawley (SD) rats were treated with FTF at doses of 0–640 µM for 24 h and 0–150 mg/kg bw/day for 28 days, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…These results suggest that the increased liver weights and macrovesicular fatty change of the hepatocytes in the HFrD group were caused by the accumulation of triglycerides in the liver. In other words, the daily consumption of excessive fructose for 4 weeks induced a typical NAFLD-like situation, as seen in other reports (12,33,34). In this study, periportal vacuolation in the hepatocytes was observed in the HFrD group after 4-weeks consumption (Table II).…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest that the increased liver weights and macrovesicular fatty change of the hepatocytes in the HFrD group were caused by the accumulation of triglycerides in the liver. In other words, the daily consumption of excessive fructose for 4 weeks induced a typical NAFLD-like situation, as seen in other reports (12,33,34). In this study, periportal vacuolation in the hepatocytes was observed in the HFrD group after 4-weeks consumption (Table II).…”
Section: Discussionsupporting
confidence: 87%
“…Body weight of flutriafol treated rats was increased compared to control at 1 and 2 wk. However, the body weights at 3 wk were not significantly different ( Kwon et al, 2021a ). No significant effects of tebuconazole treatment were observed on body condition, growth, and sex ratio of chicks ( Lopez-Antia et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to ethylated dialkylphosphates, which are known to have immunomodulatory potential, can induce long-term damage to the heart, leading to fibrosis ( Medina-Buelvas et al, 2019 ). Exposure to residual pesticides increased liver fibrosis and nonalcoholic fatty liver disease in HepG2 cells and rat liver ( Kwon et al, 2021a ; Kwon et al, 2021b ). Furthermore, meta-analysis revealed that the risk of idiopathic pulmonary fibrosis increased in agricultural workers exposed to pesticides ( Park et al, 2021 ; Ramani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that insecticide exposure impaired lipid metabolism, thereby resulting in the development of NAFLD [21]. Moreover, recent studies have reported that fungicides such as propiconazole, flutriafol, cyproconazole, dazomet, fluazinam, hexaconazole, pyrasulfotole metabolite, and myclobutanil can cause NAFLD pathogenesis [22][23][24][25]. However, the toxic effects of TEB on lipid accumulation and lipid metabolism in the liver have rarely been studied.…”
Section: Discussionmentioning
confidence: 99%